Creación de cinco postres a base de productos regionales del cantón Ibarra mediante el uso de repostería fina para su revalorización - López Flores, Nathaly Alexandra (2024)
This research focuses on the creation of five innovative desserts that incorporate regional products from the canton of Ibarra, applying fine pastry techniques. The main motivation is to revalue the local gastronomic identity by rescuing and promoting native ingredients that are often unknown or underestimated both locally and by tourists. The overall objective of this research is to create five innovative desserts, fusing products grown in the region with fine pastry techniques, to highlight the culinary richness and diversity of Ibarra, integrating traditional products such as fruits, grains and other regional ingredients, in order to encourage their consumption and promote sustainability and local economic development. The methodology employed included a documentary research phase on Ibarra's native products, followed by culinary experimentation in which advanced fine pastry techniques were applied. Tests and adjustments were made to perfect the recipes of the five selected desserts. In addition, tastings were conducted with a panel of experts to evaluate the acceptance and quality of the creations. The results show that it was possible to create five innovative desserts: Mousse au chocolat et à l'orange - Couronne de pâtes pour vélo - Mini tarte chiboust aux framboises - Bulle violette - Soirée gourmande with the following regional products: mandarin, strawberry, cocoa, pea, quinoa, orange and ataco. These were the desserts that were not only well received by the experts, but also have great potential to be marketed. The desserts developed stand out for their originality and their ability to enhance the traditional flavors of the region. It is concluded that the creation of these desserts can generate greater interest in regional products, boosting the local economy and promoting agricultural and food sustainability in the region.